THE ROLE AND IMPORTANCE OF ENGLISH AS A GLOBAL LANGUAGE IN LOCAL HIGHER EDUCATION SYSTEMS - Gulmira Makhamatiminovna Zhuraeva, (International Journal of Innovations in Engineering Research and Technology, 2026)
This article provides a comprehensive analysis of the strategic role of English in transforming local higher education systems in the context of modern globalization. The relevance of the study lies in the fact that today English serves not only as a means of communication but also as the primary driver of science and innovation. The article examines the implementation of the EMI (English as a Medium of Instruction) methodology in national higher education institutions, its advantages, and emerging linguo-methodological challenges. The author conducts a comparative analysis of the integration processes between international educational standards and the local education system, justifying the importance of the language factor in increasing students' academic mobility. Finally, practical recommendations are provided to improve the quality of English language teaching in the modern engineering and technical personnel training.